Computational and Experimental Investigation of the Optical Propeties of the Chromene Dyes; Journal of Physical Chemistry A; Vol. 119, iss. 10 - Minaev B. F.; Valiev R. R. Rashid Rinatovich; Nikonova E. N.; Gadirov R. M.; Solodova T. A.; Kopylova T. N.; Tel’minov E. N. (2015, 2015)
Title screen